Killer Timing: The Temporal Uterine Natural Killer Cell Differentiation Pathway and Implications for Female Reproductive Health - Fraser, Rupsha; Zenclussen, Ana Claudia (Frontiers in Endocrinology, 2022)
Natural killer (NK) cells are the predominant maternal uterine immune cell component, and they densely populate uterine mucosa to promote key changes in the post-ovulatory endometrium and in early pregnancy. It is broadly accepted that (a) immature, inactive endometrial NK (eNK) cells in the pre-ovulatory endometrium become activated and transition into decidual NK (dNK) cells in the secretory stage, peri-implantation endometrium, and continue to mature into early pregnancy; and (b) that secretory-stage and early pregnancy dNK cells promote uterine vascular growth and mediate trophoblast invasion, but do not exert their killing function. However, this may be an overly simplistic view. Evidence of specific dNK functional killer roles, as well as opposing effects of dNK cells on the uterine vasculature before and after conception, indicates the presence of a transitory secretory-stage dNK cell (s-dNK) phenotype with a unique angiodevelopmental profile during the peri-implantation period, that is that is functionally distinct from the angiomodulatory dNK cells that promote vessel destabilisation and vascular cell apoptosis to facilitate uterine vascular changes in early pregnancy. It is possible that abnormal activation and differentiation into the proposed transitory s-dNK phenotype may have implications in uterine pathologies ranging from infertility to cancer, as well as downstream effects on dNK cell differentiation in early pregnancy. Further, dysregulated transition into the angiomodulatory dNK phenotype in early pregnancy will likely have potential repercussions for adverse pregnancy outcomes, since impaired dNK function is associated with several obstetric complications. A comprehensive understanding of the uterine NK cell temporal differentiation pathway may therefore have important translational potential due to likely NK phenotypic functional implications in a range of reproductive, obstetric, and gynaecological pathologies.